Antibiotic resistance as a tragedy of the commons: An ethical argument for a tax on antibiotic use in humans. (20th May 2019) - Giubilini, Alberto
Abstract: To the extent that antibiotic resistance (ABR) is accelerated by antibiotic consumption and that it represents a serious public health emergency, it is imperative to drastically reduce antibiotic consumption, particularly in high‐income countries. I present the problem of ABR as an instance of the collective action problem known as 'tragedy of the commons'. I propose that there is a strong ethical justification for taxing certain uses of antibiotics, namely when antibiotics are required to treat minor and self‐limiting infections, such as respiratory tract infections, in otherwise healthy individuals. Taxation would allow a reduction in consumption (given certain behavioural economics assumptions) and/or ensure that individuals internalize or compensate for their contribution to the erosion of the common good of antibiotic effectiveness. I suggest that revenue from the tax could be used to fund conservation and innovation strategies. Taxation might be a coercive policy, especially for certain individuals, but the ethical case for coercive policies is very strong when the good to be preserved is important enough and when they force individuals to do something they have a moral obligation to do anyway. I argue that, in the case of mild and self‐limiting infections, individuals have a moral duty of easy rescue and a moral duty of fairness to make their contribution to the preservation of the common good of antibiotic effectiveness by foregoing antibiotics. I also suggest that taxing antibiotics in such cases is an all things considered ethically justified policy even if it would introduce inequalities in access to healthcare.